Characterization of PM2.5 and PM10-2.5 air pollution of Ulaanbaatar city - S. Lodoysamba; D. Shagjjamba; G. Gerelmaa (Scientific transaction of the National University of Mongolia. Physics, 2022)
Results of 2006-2007 PMs and PM10-25 aerosol pollution study of Ulaanbaatar city, Mongolia is been presented. PM 25 and PM1025 aerosol fractions have been measured twice a week at the Bayanzurkh district of Ulaanbaatar city. Weight of the samples and Black Carbon were determined at the Nuclear Research Centre (NRC), National University of Mongolia. Elemental analysis has been performed at the New Zealand Institute of Geological and Nuclear Sciences using PIXE and PIGE analysis. It includes F, Na, Mg, Al, Si, P, S, CI, K, Ca,Ti, V, Cr, Co, Ni, Cu, Zn, As, Br, Sr, Ba, I, Hg, Pb. Pollution source identification and its apportionment is been done at NRC. Main pollution sources for PM2.5 in Ulaanbaatar city is combustion (40%), soil and construction dust (38%) and auto vehicles (18-22%). Average concentration of PM10-2.5 is 147ug/m' in winter and 72-80ug/m'in summer, PM2.5 is 41-52ug/moin winter and 12-18ug/m in summer time.